ChemInform Abstract: Palladium‐Catalyzed Insertion Reactions of Isocyanides into Thiocarbamates and Selenocarbamates. Issue 42 (October 2015) - Shiro, Daisuke; Fujiwara, Shin‐ichi; Tsuda, Susumu; Iwasaki, Takanori; Kuniyasu, Hitoshi; Kambe, Nobuaki
Abstract The insertion reaction of isocyanides with thiocarbamates and selenocarbamates in the presence of a Pd(0) catalyst gives selectively 2‐oxoethanimidothioates and ‐selenoates, respectively.